Biological groundwater treatment for chromium removal at low hexavalent chromium concentrations. (June 2016) - Mamais, Daniel; Noutsopoulos, Constantinos; Kavallari, Ioanna; Nyktari, Eleni; Kaldis, Apostolos; Panousi, Eleni; Nikitopoulos, George; Antoniou, Kornilia; Nasioka, Maria
Abstract: The objective of this work is to develop and evaluate biological groundwater treatment systems that will achieve hexavalent chromium reduction and total chromium removal from groundwater at hexavalent chromium (Cr(VI)) groundwater concentrations in the 0–200 μg/L range. Three lab-scale units operated, as sequencing batch reactors (SBR) under aerobic, anaerobic and anaerobic–aerobic conditions. All systems received groundwater with a Cr(VI) content of 200 μg/L. In order to support biological growth, groundwater was supplemented with milk, liquid cheese whey or a mixture of sugar and milk to achieve a COD concentration of 200 mg/L. The results demonstrate that a fully anaerobic system or an anaerobic–aerobic system dosed with simple or complex external organic carbon sources can lead to practically complete Cr(VI) reduction to Cr(III). The temperature dependency of maximum Cr(VI) removal rates can be described by the Arrhenius relationship. Total chromium removal in the biological treatment systems was not complete because a significant portion of Cr(III) remained in solution. An integrated system comprising of an anaerobic SBR followed by a sand filter achieved more than 95% total chromium removal thus resulting in average effluent total and dissolved chromium concentrations of 7 μg/L and 3 μg/L, respectively. Highlights: Anaerobic systems provide for higher Cr(VI) removal rates compared to aerobic systems. Complete microbial Cr(VI) reduction is achieved under anaerobic conditions. Easily degradable substrates support higher Cr(VI) removal rates than complex ones. Cr(VI) removal rates follow the Arrhenius equation for temperatures between 12 °C–33 °C. Sand filtration as a polishing step provides for complete Cr removal from groundwater.